2019
DOI: 10.4067/s0717-95022019000401310
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomical Study of the Facial Artery

Abstract: The facial artery (a branch of the external carotid artery) is the main artery of the face. It gives rise to seven branches viz. inferior labial, superior labial, inferior alar, superior alar, lateral nasal and angular arteries, which are variable. This study included a dissection of twenty embalmed adult cadaveric head and neck specimens. The parameters of origin, branching patterns, termination and variations were analysed and compared with sex and laterality. The facial artery followed the standard anatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Characteristics of each study that fulfilled all criteria for inclusion are shown in Table 1. Out of 24 studies, 20 were based on cadaver dissections regarding a total of 1274 arteries in 745 cadavers (Dickson et al, 2014; Dupoirieux et al, 1999; Gardetto et al, 2002; Gocmen‐Mas et al, 2015; Koh et al, 2003; Laurentjoye et al, 2012; Lee, Gil, et al, 2015; Lee, Yang, et al, 2015; Lohn et al, 2011; Loukas et al, 2006; Midy et al, 1986; Mitz et al, 1973; Nakajima et al, 2002; Niemann et al, 2019; Niranjan, 1988; Pilsl et al, 2016; Pinar et al, 2005; Qassemyar et al, 2012; Saban et al, 2012; Tansatit et al, 2021), three on computed tomography angiography (CTA) images of a total of 726 arteries gathered from 423 patients (Furukawa et al, 2013; Hong et al, 2020; Koziej et al, 2019) and one included 119 arterial patterns gathered from 110 human fetuses (Kozielec & Józwa, 1977). In total, morphological data of 2119 arteries were included in this meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of each study that fulfilled all criteria for inclusion are shown in Table 1. Out of 24 studies, 20 were based on cadaver dissections regarding a total of 1274 arteries in 745 cadavers (Dickson et al, 2014; Dupoirieux et al, 1999; Gardetto et al, 2002; Gocmen‐Mas et al, 2015; Koh et al, 2003; Laurentjoye et al, 2012; Lee, Gil, et al, 2015; Lee, Yang, et al, 2015; Lohn et al, 2011; Loukas et al, 2006; Midy et al, 1986; Mitz et al, 1973; Nakajima et al, 2002; Niemann et al, 2019; Niranjan, 1988; Pilsl et al, 2016; Pinar et al, 2005; Qassemyar et al, 2012; Saban et al, 2012; Tansatit et al, 2021), three on computed tomography angiography (CTA) images of a total of 726 arteries gathered from 423 patients (Furukawa et al, 2013; Hong et al, 2020; Koziej et al, 2019) and one included 119 arterial patterns gathered from 110 human fetuses (Kozielec & Józwa, 1977). In total, morphological data of 2119 arteries were included in this meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Additional statistics were performed for FA termination as a lateral nasal or angular artery after dividing type 3 into two subtypes. For this purpose, only the data from studies that clearly separated lateral nasal and angular artery in their results were used (Dickson et al, 2014; Dupoirieux et al, 1999; Gocmen‐Mas et al, 2015; Hong et al, 2020; Koh et al, 2003; Laurentjoye et al, 2012; Lee, Yang, et al, 2015; Lohn et al, 2011; Loukas et al, 2006; Midy et al, 1986; Niemann et al, 2019; Niranjan, 1988; Pilsl et al, 2016; Pinar et al, 2005; Qassemyar et al, 2012; Tansatit et al, 2021), hence data regarding 1339 arterial patterns were included in these statistics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies reported six or more types (with subtypes) due to the variable course and individual differences in termination patterns [28]. Termination of the FA was ILA (5.13%), SLA (10.26%), the inferior (10.26%) and superior (46.15%) alar arteries, LNA (5.13%), and AA (20.51%) [28]. Males (48.72%) were found to have more variations than females (41.03%) [28].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative knowledge on individual anatomical variations in facial artery patterns may aid maxillofacial surgeons in reconstructive planning to effectively manage facial injuries with arterial involvement, dermatologists in aesthetic procedures, and radiological anatomy professionals in the field of malignancies for the treatment of various facial tumors by embolization [13][14][15][16]. Information on variations in the facial artery may also contribute to damage risk mitigation during cosmetic procedures such as neurotoxin or filler injections [17,18].…”
Section: Introductionmentioning
confidence: 99%